The reality of family planning services in the city of Lattakia and its countryside " Demographic comparative study in the clinics of Lattakia 2010-2015" - Shuraiki, Mada; Shaheen , Celine (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The heath centers (clinics) play a leading role in providing family planning services, as well as other governmental health institutions, and some private and non-governmental organizations. Because of this leading role, it’s important to study these centers, in order to explore and perceive the actuality of the services they offer in the areas of family planning and reproductive health. Actually, the governmental sector in the Syrian Arab Republic has an important role in these fields of healthcare. On the other hand, It’s known that the country is passing through critical times since the beginning of the Syrian crisis in 2011, this crisis has created a new demographic situation, related – among others – to the huge displacement of Syrians towards more secure regions, and to the destruction of many health centers that became out of service. In this context, this study tries to represent the reality of the health care provided by the clinics in the fields of pregnancy follow up and the providing of family planning methods during the years from 2010 to 2015, it aims to do some comparisons to enlighten the differences among the clinics in Lattakia’s urban and rural centers during the period of the study.